2012
DOI: 10.1371/journal.pone.0043372
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 Haploinsufficiency Ameliorates the Development of Ossification of the Posterior Longitudinal Ligament

Abstract: Ossification of the Posterior Longitudinal Ligament (OPLL) is a disease that is characterized by the ectopic calcification of the ligament; however, the pathogenesis of OPLL remains to be investigated. We attempted to identify the in vivo role of Runx2, a master regulator of osteoblast differentiation and skeletal mineralization, in the pathogenesis of OPLL. The expression of Runx2 in the ligament was examined using in situ hybridization and immunohistochemistry and by monitoring the activity of a LacZ gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…6g). We examined the expression of runx2 by real time PCR, given runx2 is an early bone marker that is upregulated in heterotopic ossification of other soft tissues (15,26). Compared to TMJ disc cells in basal media, runx2 upregulated by 13.5 fold in TMJ disc cells in osteogenic media (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6g). We examined the expression of runx2 by real time PCR, given runx2 is an early bone marker that is upregulated in heterotopic ossification of other soft tissues (15,26). Compared to TMJ disc cells in basal media, runx2 upregulated by 13.5 fold in TMJ disc cells in osteogenic media (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…32 Based on the understanding about the significance of Runx2 in normal formation of osteoblasts, investigations related to osteoblastrelevant disorders (e.g., OPLL) demonstrated that haploinsufficiency of Runx2 could impede development of OPLL in ENPP1 ttw/ttw mice, implying that normal Runx2 expressions may be essential to trigger OPLL. 33 In addition, research findings of Kishiya and his colleagues indicated that Runx2 might play a regulatory role in ectopic calcification through regulation of a downstream effector (i.e., angiopoietin-1), giving a hint that Runx2 could act as a critical regulator for the development and progression of OPLL. 7 However, previous researches were still insufficient to explain how Runx2 is linked with OPLL through its physiological and pathological roles.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, heterotopic calcification of ligaments and tendons is associated with diseases such as ossification of the posterior longitudinal ligament (OPLL) and calcific tendinopathy (CTP). Runt‐related transcription factor 2 (Runx2) is expressed in OPLL‐like regions, and its elevation is a prerequisite for developing a complete OPLL‐like phenotype (Iwasaki et al , ). Heterotopic calcification in CTP is associated with collagenase‐induced degenerative tendon (Lui et al , ).…”
Section: Discussionmentioning
confidence: 99%